Defining the concept of reserve in the motor domain: a systematic review - Giustiniani, Andreina; Quartarone, Angelo (Frontiers in Neuroscience, 2024)
A reserve in the motor domain may underlie the capacity exhibited by some patients to maintain motor functionality in face of a certain level of disease. This plasticity-based form of "motor reserve" (MR), could include cortical, cerebellar and muscular processes. However, a systematic definition has not been provided yet. Clarifying this concept in healthy individuals and patients would be crucial for implementing prevention strategies and rehabilitation protocols. Due to its wide application in the assessment of the motor system functioning, noninvasive brain stimulation (NIBS) may support such definition. Here, studies focusing on reserve in the motor domain and studies using NIBS were revised. Current literature highlights the ability of the motor system to create a reserve as well as a possible role for NIBS. MR could include several mechanisms occurring in the brain, in the cerebellum and in the muscles and NIBS may support the understanding of such mechanisms.